Experience with Chronic Pelvic Pain (TAJ: Journal of Teachers Association, 2009)
A 12-month study was carried out on 500 patients attending between January 2006 to December 2006 in a private chamber in Rajshahi and outpatient Department of Gynecology and Obstetrics of Rajshahi Medical College. The aim of the study was to assess the frequency of chronic pelvic pain and cause of chronic pelvic pain among the patients attending there. Among the 500 recruited patients 20% had organic cause; the rest 80% had no organic cause. Among the recruited patient, only 20% underwent surgery & improved after surgery. It was also found that another 60% improved with medical treatment, psychotherapy and counseling. doi: 10.3329/taj.v21i2.3789 TAJ 2008; 21(2): 118-120